Functional Properties of Instant Yellow Rice of Gembili Tubers (Dioscorea esculenta) to Improve Food Security - Wardani, Retno Kusuma; Subariyatun, Siti; Azhari, Salma Widya; Sofyan, Aan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2021)
Gembili tubers have sufficient carbohydrate content compared to other tubers. Gembili tubers contain bioactive compounds that can be beneficial for the body. The antioxidants contained in gembili tubers are phenol, diosgenin, and dioscorin. Dietary fiber is also contained in gembili tubers which can provide benefits for the body such as overcoming diabetes, preventing digestive disorders, lowering cholesterol levels. These tubers can be processed into tuber flour, starch, and composite flour. In addition, this tuber can be used as an alternative non-rice food source. Turmeric as a colorant for instant yellow rice of gembili tubers which contains antioxidants, anti-inflammatory, antimutagenic, anticancer, and antimicrobial properties. So far, no one has made instant yellow rice made from gembili tubers. Purpose: The research is aimed to determine the content of antioxidants activity and dietary fibers in instant yellow rice from gembili tubers with different drying temperature variations of 70oC, 80oC, and 90oC. Methodology: The experiment of instant yellow rice was conducted using a single-factor Completely Randomized Design (CRD) method with temperature variations of 70oC, 80oC, and 90oC for three hours. Testing of dietary fiber using the multienzyme method and testing of antioxidant activity using the RSA IC50 method. The research was carried out in two treatment replications with two laboratory analyzes. Furthermore, the obtained data were analyzed using the One-Way ANOVA test, and if the results showed a treatment effect, then proceed using the DMRT test with = 5%. Results: The results of this study showed that the dietary fiber content of instant yellow rice from Gembili tubers had no effect on variations in drying temperature with p = 0.685 (p ≥ 0.05). However, based on three different temperature treatments, the highest dietary fiber content was at 70OC temperature treatment, which was 10.8047%. Whereas antioxidant activity tests on instant yellow rice of Gembili tubers indicated that there was an effect of drying temperature variations on antioxidant activity with p = 0.001 (p < 0.05). The variation of the drying temperature of 90OC shows the highest antioxidant activity, which is 6162,7008 ppm. The lower of the drying temperature, so the lower of the level antioxidant activity. Applications/Originality/Value: This diversification product of instant yellow rice of gembili tubers is expected can support the national food security program by reducing rice consumption rate without causing substantial change in the tradition of the Indonesian people.